Relativistic traveling wave tubes of O-type with sheet electronic beams - A. V. Aksenchyk; I. F. Kirinovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The mathematical model of calculation of relativistic traveling wave tubes (TWT) of O-type on folded rectangular waveguides with sheet electronic beams taking into account a space charge was formulated. Parameters optimization was spent and the maximum efficiency of variants of devices for the different sizes of the electronic beam, accelerating voltages 500 kV, currents of electronic beam 200 A were obtained. It was shown, that the efficiency of one- and two-section TWTs can reach of 56 %, gain - of 30-50 dB.